KARAKTER TEKNOLOGI LITIK HOMO ERECTUS PROGRESIF BERDASARKAN HIMPUNAN ARTEFAK DARI SITUS MATAR, BOJONEGORO - M. Ruly Fauzi; M. Fadhlan S. Intan; Truman Simanjuntak (KALPATARU, 2015)
The 20 meter-high Solo terrace claimed to be Upper-Pleistocene deposit has often been discussed since the discovery of 14 Homo erectus specimens with numerous artifacts in Ngandong on 1931-1933. Nevertheless, the artifacts that have been baptized as implements of progressive Homo erectus is rarely discussed, especially the character of their technology, which remains unclear. Matar, a new site situated on the eastern banks of Solo River with similar lithology and position to those of Ngandong, provides new data related to lithic artifacts. Analysis on lithic assemblage from Matar locality was aimed at characterizing morphology and technology of the implements of progressive Homo erectus. Specified analysis consisting of typology and measurements of flake artifacts successfully shows its specific characteristics. Measurements on flakes show débitage products that tend to be rectangular and slightly elongated. In general, the lithic assemblage from Matar shows the presence of flakes together with massive tools such as bola, spheroidal, polyhedrons, and chopper-chopping tools. The presence Oldowanian massive tools might indicate their exceptional utility that could not be replaced by flakes in progressive Homo erectus culture. Teras 20 meter Bengawan Solo yang diklaim berumur Pleistosen Atas seringkali dibahas sejak penemuan 14 spesimen Homo erectus beserta sejumlah artefak di Ngandong pada tahun 1931-1933. Namun demikian, artefak batu yang dianggap sebagai peralatan Homo erectus progresif tersebut jarang sekali dibahas secara khusus, sehingga karakter teknologi mereka masih belum jelas statusnya. Situs Matar di tepi timur Bengawan Solo dengan litologi dan posisi yang mirip dengan Ngandong memberikan data baru terkait artefak litik dengan taksiran umur yang sama. Analisis terhadap himpunan artefak litik Situs Matar bertujuan untuk mengetahui karakter bentuk dan teknologi artefak litik Homo erectus progresif. Analisis khusus berupa tinjauan tipologi dan dimensi artefak serpih menunjukkan ciri khusus. Pengukuran serpih menunjukkan produk débitage yang cenderung rektangular dan sedikit memanjang. Secara umum, himpunan artefak litik dari Matar menunjukkan kehadiran alat serpih bersama dengan artefak masif seperti bola, spheroidal, polihedron, serta kapak perimbas-penetak. Kehadiran alat masif bercirikan Oldowanian tersebut menunjukkan fungsi alat yang sepertinya tidak tergantikan oleh artefak serpih di dalam budaya Homo erectus progresif.